The Implication of Generative Artificial Intelligence towards Intellectual Property Rights (Examining the Multifaceted Implications of Generative Artificial Intelligence on Intellectual Property Rights) - Priscilla Auleader Napitupulu; Clara Alrosa Fernanda Sinaga; Albert Lukas Pithel Hasugian (Westscience Press, 2023)
Generative Artificial Intelligence (Generative AI) is transforming content creation, enabling faster and cheaper production of text, images, and more. However, it raises complex issues regarding intellectual property rights and ownership. This article explores the evolving landscape of AI-generated content, focusing on its alignment with existing intellectual property regulations. It delves into legal disputes exemplified by cases like Getty Images, INC. v. Stability AI, INC, and Doe v. Github, INC, which highlight the challenges of AI-generated content regarding intellectual property. The article also discusses the impact on the creative sector and offers recommendations, including the need for ethical guidelines, education, hybrid collaboration, public involvement, and international cooperation. Addressing these challenges is crucial to harmonize intellectual property rights and maximize the benefits of AI in content creation.